ANALISIS PERBEDAAN HARGA SAHAM SEBELUM DAN SESUDAH PEMILIHAN UMUM PRESIDEN 2014 (Event Study Pada Sektor Jasa Keuangan Yang Listing Di Bursa Efek Indonesia) - Ida Mentayani; Rusmanto Rusmanto; Ridho Ridhani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aims to provide empirical evidence about whether there is any difference in the share price and the average share price difference before and after the 2014 presidential elections in the financial services sector listing on the Indonesia Stock Exchange. The population used in this research is the company's financial services sector consists of three sub-sectors, namely banking sub-sector, sub-sector and sub-sector insurance financing totaling 65 companies. Methods of sample selection using purposive sampling techniques that amounted to 30 companies. Method of Paired-Sample T-Test is used to test the hypothesis in order to determine differences in stock prices before and after the 2014 presidential elections in the financial services sector listing on the Indonesia Stock Exchange. The results of the research provides empirical evidence that there are differences in stock prices before and after the 2014 presidential elections in the financial services sector listing on the Indonesia Stock Exchange. Hypothesis testing is done with a statistical test or t test where t values of -2941 with a significance of 0.004 which is less than 5% or 0.05 so that the hypothesis can be accepted. The average share price prior to the presidential election in 2014 of the period of the H-10 to H-1 at 1.6397, while the average stock price the financial services sector after the presidential election in 2014 of the period D + 1 to D + 10 at 1.6644 , So that the average stock price after the 2014 presidential elections is higher than before the 2014 presidential election.